2012
DOI: 10.1002/chem.201202391
|View full text |Cite
|
Sign up to set email alerts
|

Guest Covalent Capture by a Host: A Biomimetic Strategy for the Selective Functionalization of a Cavity

Abstract: A biomimetic strategy for the monofunctionalization of a calix[6]arene core is described. It is based on host-guest chemistry (mimicking the Michaelis-Menten adduct in enzymes) and allows the finely tuned pre-organization of the substrate (an alkyne) with respect to the reactant (three azido groups introduced at the calixarene large rim). It is shown that the thermal Huisgen reaction implemented in this work proceeds under very mild conditions with total regioselectivity of the cycloaddition process. The scope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…[40] If after reactionc omplex formation is prevented, significant selectivity for monofunctionalization can be achieved.C ovalent capture with native CDs was initially demonstratedb yB ender et al,w ho observed as ignificant rate acceleration for the acylation reactiono fb-CD with m-nitrophenylacetate compared to the rate of background ester hydrolysis, and has since been successfully applied for CD-based catalysis. [41,42] This approach has also been used to monofunctionalize ac alix [6]arene core, with variousg uests through as elective Huisgen cycloaddition reaction. [43,44] Using covalent capture, we reported the selectivem onoderivatization of heptakis[6-deoxy-6-(2-aminoethylsulfanyl)]-b-CD (1).…”
Section: Introductionmentioning
confidence: 99%
“…[40] If after reactionc omplex formation is prevented, significant selectivity for monofunctionalization can be achieved.C ovalent capture with native CDs was initially demonstratedb yB ender et al,w ho observed as ignificant rate acceleration for the acylation reactiono fb-CD with m-nitrophenylacetate compared to the rate of background ester hydrolysis, and has since been successfully applied for CD-based catalysis. [41,42] This approach has also been used to monofunctionalize ac alix [6]arene core, with variousg uests through as elective Huisgen cycloaddition reaction. [43,44] Using covalent capture, we reported the selectivem onoderivatization of heptakis[6-deoxy-6-(2-aminoethylsulfanyl)]-b-CD (1).…”
Section: Introductionmentioning
confidence: 99%
“…The ligands L X (X = OH, NH 2 ) that were studied in this work were prepared according to a host-guest covalent-capture approach. [10] Two sets of ligands are appended onto the calixarene skeleton: At the small rim, a tris-imidazolyl coordination site is present and, at the large rim, a fourth ligand that is able to interact with the metal cation through the cavity is attached through a triazole unit ( Figure 1). Thus, we anticipated that endo coordination of the appended arm would occur if the coordinating strength of the terminating X group were higher than that of residual water (or coordinating solvent), assuming the formation of a mononuclear Cu II species.…”
Section: Resultsmentioning
confidence: 99%
“…[9,10] We demonstrated that the nature of the appended functional group (hydroxy or amino) tuned the access of an exogenous guest ligand to the zinc metal centre that was buried inside the cavity. [10] Herein, we couple the host-guest properties of calix[6]-based Ouroboros-like copper complexes to the control of their oxidation states. Two different monofunctionalised calix [6]arene ligands, L X (X = OH, NH 2 ; Figure 1), are used for probing the influence Keywords: calixarenes · copper · host-guest systems · ligand effects · redox chemistry Abstract: The conformation of copper "funnel" complexes that contains a coordinating appended arm can be electrochemically switched between endo, which corresponds to the self-coordination of the arm through the cavity, and exo positions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the ditopic targeted ligand Felix followsa n approacht hat was previously shown to be efficient and versatile for the selectivei ntroductiono fasingle functional group at the small rim of the calix [6]arene core (Scheme 1). The key step for the selective functionalization of the macrocycle relies on the "guest covalent capture by ah ost"s trategy, [26][27][28] starting with the triazido derivative 1 of ac alix [6]arene-based tris(imidazole) ligand.T he corresponding Zn II complex was reacted with an amino-alkyne bearing ah ydroxymethyl substituent at its end. Heatingt he corresponding host-guest complex ((1)Zn(guest) 2 + ,S cheme 1) yielded as ingle product.…”
Section: Ligand Synthesismentioning
confidence: 99%